Prevalence and patterns of premenstrual disorders and possible association with sexual harassment: a cross-sectional study of young Arab women - Yossef Hassan AbdelQadir; Ahmed Assar; Yomna Ali Abdelghafar; Manar Ahmed Kamal; Mohamed Sayed Zaazouee; Sarah Makram Elsayed; Khaled Mohamed Ragab; Ayman Essa Nabhan; Nahla Ahmed Gamaleldin; IMedRA collaborators team (BMC, 2022)
Abstract Background Premenstrual syndrome (PMS) and premenstrual dysphoric disorder (PMDD) represent a range of both psychiatric and physical symptoms that impair quality of life and interfere with daily activities in females. Aims To assess the prevalence of PMS and PMDD in Egypt, Jordan and Syria, its demographic associations and the potential link to sexual harassment (SH). Methods We used an Arabic version of the premenstrual symptoms screening tool (PSST) to assess the prevalence of PMS and PMDD. Another two-part questionnaire was used to assess the harassment experience. Results 22,021 women agreed to fill the questionnaire; the majority (65%) aged 18-25 years old. PMS was more prevalent in Egyptian women 77.7% followed by women from Jordan 72.9% then Syria 66.3%. PMDD prevalence followed the same order (40%, 34.7% and 28.2%). Both conditions were significantly associated with obesity and working in medical careers (P = .001). 5733 women agreed to share their sexual harassment experience. Results showed a significant association between the diversity and frequency of sexual harassment and the frequency of the pre-menstrual conditions, PMS Frequency was 87.6%, 80.7% and 78% in participants who were harassed on daily basis Vs. once weekly or monthly vs. few times in their lifetime (p = .04). A similar statistically significant difference was noticed regarding having PMDD (66.4% vs. 47.6% vs. 42.5%). Conclusion The study showed high levels of both PMS and PMDD. The data provided by this study also sheds light on a potential link between SH and developing Pre-menstrual disorders.